Long-Term Outcomes of Gastric Endoscopic Submucosal Dissection: Focus on Metachronousand Non-Curative Resection Management - Libânio,D. (2017)
Introduction: Endoscopic submucosal dissection (ESD) is an effective treatment for gastric superficial neoplasms and curative in 80-85% of the patients. The aims of this study were to identify risk factors for non-curative resection and metachronous development, and to evaluate patient management and outcome after non-curative resection. Methods: In this single-centre study, the outcome of consecutive patients submitted to gastric ESD was assessed during a minimum follow-up of 18 months. Univariate analysis and multivariate logistic regression were performed to identify risk factors. Results: ESD was performed in 194 lesions (164 patients) between 2005 and 2014. The median follow-up was 40 months. En bloc and complete resection rates were 95.3 and 93.8%, respectively. Male sex, larger tumor size, longer procedural time, and more advanced histology were associated with a non-curative resection ( p < 0.05), but only carcinoma detected in biopsies before resection was identified as a significant risk factor on multivariate analysis. Metachronous lesions occurred in 18.4%, and the incidence rate was 4.7 lesions/100 person-years. Older age at diagnosis was identified as the only predictor of metachronous development in logistic regression. In the non-curative resection group, survival did not differ between patients allocated to surveillance and those submitted to gastrectomy; 75% of gastrectomy specimens showed no residual lesion. Conclusions: The risk factors identified for non-curative resection help to improve patient selection and patient information. Older patients had an increased risk for the development of metachronous lesions. In patients with non-curative resections, individualized patient management and surveillance seems to be an adequate option in selected cases.